2021
DOI: 10.1038/s41598-021-02678-1
|View full text |Cite|
|
Sign up to set email alerts
|

A large-scale population-based epidemiological study on the prevalence of central sensitization syndromes in Japan

Abstract: A cross-sectional study of 21,665 Japanese residents was performed to investigate the prevalence of central sensitization syndromes (CSS). CSS were assessed using the Central Sensitization Inventory (CSI-A). CSS were defined as a CSI-A score of 40 or higher. Age, sex, district, 10 CSS-related diseases (CSI-B), lifestyle, and mental factors were rated in a self-reported survey. The prevalence of CSS and its relationship with potential factors were examined by sex using descriptive and logistic regression models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
5
6
0
Order By: Relevance
“…One aim of this study was to investigate the characteristic of subgroup based on the severity of pain and CSS, and this study showed that more women were in the mild pain/severe pain group and fewer women were in the severe pain/mild pain group. The severity of CSS in women has previously been demonstrated in studies of musculoskeletal pain patients and healthy individuals 16 18 and has similar results to the present study. However, the severity of CSS in the severe pain/CSS group was not significantly higher than that in the other groups, although the proportion of females was higher (66%).…”
Section: Discussionsupporting
confidence: 91%
“…One aim of this study was to investigate the characteristic of subgroup based on the severity of pain and CSS, and this study showed that more women were in the mild pain/severe pain group and fewer women were in the severe pain/mild pain group. The severity of CSS in women has previously been demonstrated in studies of musculoskeletal pain patients and healthy individuals 16 18 and has similar results to the present study. However, the severity of CSS in the severe pain/CSS group was not significantly higher than that in the other groups, although the proportion of females was higher (66%).…”
Section: Discussionsupporting
confidence: 91%
“…Our study sample consisted only of females, so extrapolation to men is not applicable. A large epidemiological study in the general population showed a significantly higher prevalence of CS measured with CSI in females (4.2%) than in males (2.7%) [17], with a similar rate of 4% obtained in our female population of healthy controls.…”
Section: Discussionsupporting
confidence: 85%
“…This hypothesis would be in line with the observed higher prevalence of certain chronic pain conditions exhibiting ongoing CS processes in women, such as fibromyalgia, knee osteoarthritis, headache disorders, and musculoskeletal disorders. 6,10,25,44,82,92 The present findings thus underscore that sex-specific CS differences should be taken into account when (1) characterizing aetiology in chronic pain and (2) improving therapeutic approaches in patients in the future, expanding previous recommendations. 68,92…”
Section: Discussionsupporting
confidence: 60%
“…This hypothesis would be in line with the observed higher prevalence of certain chronic pain conditions exhibiting ongoing CS processes in women, such as fibromyalgia, knee osteoarthritis, headache disorders, and musculoskeletal disorders. 6,10,25,44,82,92 The present findings thus underscore that sex-specific CS differences should be taken into account when (1) characterizing aetiology in chronic pain and (2) improving therapeutic approaches in patients in the future, expanding previous recommendations. 68,92 Because only a subgroup of chronic pain conditions with CS predominantly affects women, 6,10,41,69,105 further research should be directed at understanding which additional contributors might influence CS processes to potentially become a driving factor in chronic pain.…”
Section: Potential Implications For Chronic Painsupporting
confidence: 55%